Time-resolved extreme ultraviolet emission from a highly ionized lithium capillary discharge - Marconi, Mario Carlos, author; Rocca, Jorge J., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1989)
A fast discharge current pulse (50 ns FWHM) was used to create a highly ionized plasma in a 500-μm-diam lithium hydride capillary 3.8 cm in length. Time-resolved extreme ultraviolet spectra of the capillary plasma show simultaneous line emission from highly ionized (O VI) and singly ionized (O II) species, indicating the existence of a hot-core plasma (Te>25 eV) surrounded by a significantly cooler plasma near the walls. The intensity of the 72.9 nm emission corresponding to the Li III 3-2 transition was observed to increase during the decay of the current pulse, consistent with excitation by electron-ion recombination. The results are relevant to the possibility of amplification of extreme ultraviolet radiation in a discharge-pumped device.
Keywords: ultraviolet radiation; lithium hydrides; plasma production; ultraviolet spectra; lithium ions; recombination; electric discharges